Rejouer le paysage - Arsène Caens (Projets de Paysage)
Although the history of modernity has engendered an episteme of the representations of the practices in the sciences and the arts and of our ordinary ways of relating to the world, ethnographic research on landscape representation has remained limited. The concrete, ordinary situation of the human body as it acts on, perceives the landscape, and verbalises its perception of it would allow us to account for the complexity of local uses, common knowledge and the practices of symbolisation often involved in the elaboration of our relationship with the perceived object. We can thus study the practice of actors in the poetic domain from a new perspective. Highlighting, in the same way as practised in ethnomethodology, the conversational dimension of the processes in the production of meaning that ordinarily structures practical action. We will raise the following questions : Does the poetic experience of places not rest on a substratum of communicative resources common to all social actors ? How does a referential domain specific to poetic activity nevertheless emerge from the ordinary resources of oral conversation ? What is required of a poem for it to be able to say something about a relationship with the landscape ?